RESILIENCE AND RESISTANCE: A STUDY OF PARTITION TRAUMA IN SABIHA SUMAR’S KHAMOSH PANI - D, Greeshma; D., Vijayaraghavan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper aims to analyze the film Khamosh Pani by Sabiha Sumar, focusing on the character of Veero/Ayesha and her experiences before and after the Partition of India in 1947. The paper delves into how Veero/Ayesha navigates trauma, assimilation, and identity crisis in the aftermath of Partition, particularly in the context of changing political landscapes in Pakistan, such as during the Zia-ul-Haq regime. The paper also explores themes of resilience, patriarchy, and the enduring impact of historical events on individual lives, especially women’s experiences. Through a close reading of the film and its characters, the paper seeks to shed light on the complexities of post-Partition society and the challenges faced by marginalised individuals, particularly women, in finding agency and dignity in the face of adversity.